Evaluasi Penggunaan Antibiotik pada Pasien Rawat Inap di Bangsal Penyakit Dalam RSUD. Dr. H. Abdul Moeloek Provinsi Lampung - Dirga, Dirga; Khairunnisa, Sudewi Mukaromah; Akhmad, Atika Dalili; Setyawan, Irfanianta Arif; Pratama, Anton (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2021)
The high prevalence of infectious disease in Indonesia causes increased use of antibiotics. It has serious consequences since it can cause germicidal resistance rapidly increased, significant morbidity and mortality, as well as high additional medical costs per year. This study aims to evaluate the appropriateness of antibiotic use inpatients in the internal medicine ward of Dr. H. Abdul Moeloek in Lampung Province. This research was observational (non-experimental) with a descriptive evaluative research design. The data were obtained from the retrospective tracing of medical records that collected by a purposive sampling technique on July-December 2017. A total of 163 inclusion samples are analyzed qualitatively and quantitatively. The qualitative analysis uses standard guidelines for the use of antibiotics and quantitative analysis uses the anatomical therapeutic chemical (ATC)/Defined Daily Dose (DDD) method. The results showed that out of 168 medical records, 19 types of antibiotics were used with a 118.57 DDD value of 100 patient days. The most widely prescribed was ceftriaxone (49.09%). The highest number of infections was diabetic ulcers with an incidence of 42 cases (25%). Out of 168 evaluated cases, 166 cases (98.8%) were appropriate indication, 168 cases (100%) were appropriate patients, 150 cases (89,29%) were appropriate medication, and 89 cases (52,97%) were appropriate dosage. These results indicated that the use of antibiotics inpatients in the internal medicine ward of Dr. H. Abdul Moeloek in Lampung Province were rational but it was necessary to consider selectivity regarding the choice of antibiotic use for infected patients.